Nutritional approaches in tackling hypertension - Lazarou, Chrystalleni; Kouta, Christiana (My University, 2008)
There is sufficient evidence to suggest that dietary approaches may help to prevent and control high blood pressure. This review focuses on the main dietary approaches for which there is ample scientific data regarding the prevention and management of hypertension: i.e. moderate use of sodium, alcohol, an increased potassium intake, plant fibers, calcium (and dairy products) and adherence to healthy dietary patterns such as Dietary Approaches to Stop Hypertension and the Mediterranean diet; in addition, the study also presents evidence regarding other nutritional factors which may possibly be associated with levels of blood pressure, but for which there is as yet insufficient current scientific evidence to support the issue of specific dietary recommendations. Finally, further implications for community nursing practice are discussed.